2019
DOI: 10.1098/rstb.2019.0070
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of insect metamorphosis: a developmental and endocrine view

Abstract: Developmental, genetic and endocrine data from diverse taxa provide insight into the evolution of insect metamorphosis. We equate the larva–pupa–adult of the Holometabola to the pronymph–nymph–adult of hemimetabolous insects. The hemimetabolous pronymph is a cryptic embryonic stage with unique endocrinology and behavioural modifications that probably served as preadaptations for the larva. It develops in the absence of juvenile hormone (JH) as embryonic primordia undergo patterning and morphogenesis, the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 83 publications
5
121
1
2
Order By: Relevance
“…In contrast, while Broad showed low expression in L1 as previously reported [257], expression was exceptionally low in P1-a finding that may be explained by P1 age at time of sampling [257]-and appeared to be associated with the young adult (Additional file 2: Table S22). This finding differs from previous findings for F. occidentalis adults [257] and Holometabola [258]. It may be that the broad transcript quantified in our dataset was one of possibly multiple isoforms that play a role in other processes, such as nutritional or steroid signaling associated with reproduction reported for other insects [259], but this remains to be investigated.…”
Section: Postembryonic Developmentcontrasting
confidence: 99%
“…In contrast, while Broad showed low expression in L1 as previously reported [257], expression was exceptionally low in P1-a finding that may be explained by P1 age at time of sampling [257]-and appeared to be associated with the young adult (Additional file 2: Table S22). This finding differs from previous findings for F. occidentalis adults [257] and Holometabola [258]. It may be that the broad transcript quantified in our dataset was one of possibly multiple isoforms that play a role in other processes, such as nutritional or steroid signaling associated with reproduction reported for other insects [259], but this remains to be investigated.…”
Section: Postembryonic Developmentcontrasting
confidence: 99%
“…Uyehara et al (2017) have recently shown that E93 directly acts on the chromatin structure in the enhancers of specific genes, opening up some adult-specific genes such as nubbin (important in wing vein formation) for activation and closing the chromatin on others such as broad, thus suppressing its expression. Broad and E93 are pupal-and adult-specifying transcription factors respectively throughout the Holometabola (Truman and Riddiford, 2019;Bellés, 2020) and thus fulfill the prediction of Williams and Kafatos (1971) that there are three master regulatory genes that successively activate the larval, pupal, and adult gene sets as metamorphosis proceeds. The idea that the unique features of the larva, pupa, and adult were the results of stage-specific gene sets was nullified by the finding that the same cuticle gene was expressed in the epidermis of two different metamorphic stages to produce a particular type of cuticle (Willis, 1986).…”
Section: Drosophila Development Jh and Stage-specifying Transcriptiosupporting
confidence: 68%
“…Although initially discovered in Drosophila as important for metamorphosis (Pecasse et al, 2000), Kr-h1 is present throughout the insects including the primitive firebrat, Thermobia domestica (Konopova et al, 2011), and is necessary to prevent precocious metamorphosis (Minakuchi et al, 2009;Lozano and Belles, 2011). Kr-h1 appears in the embryo at the time that JH appears and is present throughout larval life, then disappears during metamorphosis to the pupa (see review by Truman and Riddiford, 2019). The presence of JH ensures that Kr-h1 will appear when 20E rises for the larval molt and may stabilize Kr-h1 during the larval intermolt period.…”
Section: Drosophila Development Jh and Stage-specifying Transcriptiomentioning
confidence: 99%
See 1 more Smart Citation
“…The hormonal control of insect metamorphosis involves changing interaction between two hormonal systems: ecdysone for control of cuticle moulting and sesquiterpenoids (juvenile) hormones implicated in post-embryonic growth and differentiation 48 . We have focused on the putatively interacting sesquiterpenoid pathway, especially since in insects, sesquiterpenoids control the transition between developmental stages and are essential for reproduction [48][49][50] . Derived from an acetate precursor through the mevalonate pathway, farnesyl units are converted to cholesterol and steroid hormones in vertebrates, or into sesquiterpenoid hormones such as juvenile hormone in insects 51,52 (Fig.…”
Section: Resultsmentioning
confidence: 99%